ANALISIS KRITIS SUBSTANSI DAN IMPLEMENTASI UNDANG-UNDANG NOMOR 13 TAHUN 2012 TENTANG KEISTIMEWAAN DAERAH ISTIMEWA YOGYAKARTA DALAM BIDANG PERTANAHAN - Kus Sri Antoro (BHUMI: Jurnal Agraria dan Pertanahan, 2015)
Abstract: The structure of land tenure and ownership in Special Province of Yogyakarta (Daerah Istimewa Yogyakarta/DIY) haschanged radically since The Law No 13/2012 on Yogyakarta’s Special Status (UUK DIY) was enacted.. The changes include 1)establishment of both the Sultanate (Kasultanan) and Pakualaman Regency as special legal bodies allowed to possess lands,according to this article by the name of Culture Heritage Legal Body (Badan Hukum Warisan Budaya/BHWB); 2) establishmentof the existence of lands categorized as Sultan’s (Sultanaat Grond/SG) and Pakualaman’s (Paku Alamanaat Grond/PAG). Thispaper is the result of a community desk study conducted from September 2014 to February 2015, and is aimed at showing:1) the legal position of SG and PAG; 2) the legal position of state-controlled lands; 3) the legal position of lands belonging tosociety, either individual or communal (village-owned lands), 4) the position of agrarian law to UUK DIY. The analysis of officialdocuments carried out using historical; legal; and social-cultural approaches to critically analyze the substance and implementationof UUK DIY.Keywords: UUK DIY, Kasultanan, Pakualaman, Sultanaat Grond, Paku Alamanaat GrondAbstrak: Struktur penguasaan dan kepemilikan tanah di Propinsi Daerah Istimewa Yogyakarta (DIY) mengalami perubahanmendasar sejak UU No 13 Tahun 2012 tentang Keistimewaan DIY (UUK DIY) disahkan. Perubahan tersebut meliputi 1)penetapan Kasultanan/Kadipaten (Pakualaman) sebagai badan hukum khusus yang dapat memiliki tanah, dalam tulisan ini disebutBadan Hukum Warisan Budaya (BHWB); 2) pengukuhan eksistensi tanah-tanah yang digolongkan sebagai Sultanaat Grond (SG)dan Paku Alamanaat Grond (PAG). Tulisan ini merupakan hasil dari penelitian pustaka oleh komunitas masyarakat yang dilakukandari September 2014 hingga Februari 2015, dan bertujuan untuk menunjukkan 1) kedudukan hukum dari tanah dengan statusSG dan PAG; 2) kedudukan hukum dari tanah yang dikuasai negara, 3) kedudukan hukum dari tanah yang dimiliki masyarakat,baik individu maupun komunitas (tanah desa), 4) kedudukan hukum agraria terhadap UUK DIY. Analisis terhadap isi dokumendokumenresmi dilakukan dengan pendekatan sejarah, hukum, dan sosial budaya untuk menelaah secara kritis substansi danimplementasi UUK DIY.Kata kunci: UUK DIY, Kasultanan, Pakualaman, Sultanaat Grond, Paku Alamanaat Grond